Identification and utilization of informative EST-SSR markers for genetic purity testing of coconut hybrids - B.A. Jerard, K. Samsudeen, P.Preethi, M.K.Rajesh, C.U.Rahul,; A. Karun, R.J. Thomas (Journal of Plantation Crops, 2016)
Coconut palms are categorized into two forms, viz., ‘talls’ and ‘dwarfs’ which are being utilized to produce hybrids through the process of inter-varietal or intra-varietal crosses. Hybrid coconut seedlings are generally identified and selected based on morphological traits by plant breeders, which is quite difficult and requires expertise. Even minor errors in identification may adversely affect breeding programs in coconut, which is spread over many decades. In this study, we have utilized thirty EST-SSR markers, derived from existing coconut leaf transcriptome data, for screening polymorphism between eighteen coconut parental lines. The polymorphic primers capable of differentiating the parental palms were then utilized successfully for assessment of purity of hybrids derived from these parents. Thus, the current study demonstrates the utility of EST-SSR markers in determining the genetic purity of hybrids in coconut.